Hacking capitalism : the free and open source software movement. - Söderberg, Johan, ....- (New York : Routledge, 2008)
The Free and Open Source Software (FOSS) movement demonstrates how labour can self-organise production, and, as is shown by the free operating system GNU/Linux, even compete with some of the worlds largest firms. The book examines the hopes of such thinkers as Friedrich Schiller, Karl Marx, Herbert Marcuse and Antonio Negri, in the light of the recent achievements of the hacker movement. This book is the first to examine a different kind of political activism that consists in the development of technology from below.